Relationship between perceived value, attitudes, and academic motivation in distance learning among nursing students in rural areas - Mohammad M. Alnaeem; Alaa Abu Atallah; Majdi Alhadidi; Iyad Salameh; Khalid AL-Mugheed; Majdi M. Alzoubi; Amany Anwar Saeed Alabdullah; Sally Mohammed Farghaly Abdelaliem (BMC, 2024)
Abstract Background Nursing students manifest a distinct level of intellect and comprehension, impacting their attitudes and perceived significance of distance learning in education. This study examined the attitudes, perceived value, and academic motivation surrounding distance learning among Jordanian nursing students, offering insights crucial to optimizing their educational journey. Methods A descriptive cross-sectional design was used. A convenience sample of 298 undergraduate Jordanian nursing students was recruited from two public universities in rural cities in south Jordan. Data were collected via self-reported instruments (June 2022 to August 2022). A Pearson correlation and independent t-test were used to examine the relationship between variables. Results The mean age of students was 20.9 years (SD = 1.16), and most students have a low perceived value of distance learning (n = 181, 60.7%). Most students (n = 179, 60.1%) have negative attitudes toward distance learning, and only 39.9% reflected positive attitudes. More than half of the participants (n = 166, 55.7%) reflected less academic motivation toward distance learning. Positive significant relationships were found between students' perceived value of distance learning and their attitudes and academic motivation toward distance learning; low perceived value of distance learning was related significantly with low attitudes (r = 0.844, p < 0.01) and less academic motivation toward it (r = 0.721, p < 0.01). Conclusion Nursing students' perceived value, attitudes, and academic motivation toward DL in rural regions is inadequate. Educators must provide valuable visions to expand the quality of health education in rural universities and improve health care.